Correlation of Sacred Architecture and Painting in Western Ukraine. - Cherkes, Bohdan; Diachok, Oksana; Panfilova, Oleksandra; Tarasiuk, Ivan (Published under licence by IOP Publishing Ltd, 2020)
This article highlights some of the results of the scientific work conducted under the direction of the Institute of Architecture and Design of the National University “Lviv Polytechnic” together with the Department of Fine Arts and Design of Ternopil National Pedagogical University, Kremenets Regional Humanities and Pedagogics Academy, Lesia Ukrainka Eastern European National University, Department of Fine Arts. Scientists are exploring sacred arts in Western Ukraine as one of the highest achievements in the work of Ukrainian architects. In particular, the article is about the Ternopil region. The aim of the article is to cover the work of architects of the Ternopil region, correlation in their creativity of architecture and painting; the introduction into the scientific circulation of data on some temples - architectural monuments and modern churches. The territory of Western Ukraine occupies a special place in the cultural and spiritual space of the state. It is located at the crossroads of European roads, has long been noted for its multinational character and wealth of faiths. Temples of different denominations are the decoration of cities and villages and enrich their architectural landscape, and in terms of potential and value of architectural heritage, it is one of the richest regions of Ukraine. One of the spiritual symbols of the city of Ternopil is a temple built in the eighteenth century - a monument of late European Baroque architecture. The building was many times on the verge of destruction; it was burned and destroyed by wars and the communist regime, but with the declaration of independence of Ukraine the shrine was revived. Modern paintings, sculptural groups, stained glass windows and other works of sacred art have transformed the sanctuary into a city beauty, attracting visitors with its grandeur and splendor. Scientists do not often turn to the creative personality of architects. Among the renowned architects of Ukraine, who have designed projects for more than 200 temple complexes, is Ternopil artist Mykhaylo Netrybyak. He combines the work of the architect with the work of the teacher, and the creative nature of the artist is reflected in the paintings. The famous painter of Ternopil with professional architectural education is Mykhaylo Kuziv, who also combines artistic work with pedagogical activity. His works are known far beyond Ukraine and are exhibited in state and public institutions, in private collections of Ukraine and in many countries of the world. Thus, as a result of the research, the data on some contemporary architects and artists of Ternopil region were put into scientific circulation; their role in the process of revival of temple construction of Ukraine is defined; it describes some of the temples – architectural monuments and modern architectural buildings.
Keywords: modern painting; Ternopil region; architectural landscape; churches